2022
DOI: 10.1186/s40359-022-01027-9
|View full text |Cite
|
Sign up to set email alerts
|

#fitspiration: a comparison of the sport-related social media usage and its impact on body image in young adults

Abstract: Background Following and posting sport-related content on social media is wide-spread among young people. To date, little is known about the interdependence between sport-related social media use and the thereby perceived personal body image. Methods We conducted an online survey (N = 285) to examine how social media influences the sport-related body image. Results In general, social media are frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Among the others, the complex relationship between EA, and SMA, perfectionism, body image disorders, and "fitspiration" construct have been studied, since 2015 (46). Interestingly, "fitspiration" diversion into a distortion of body perception could emerge (20,47,48). Although "fitspiration" generally conveys positive messages, the images associated with that may have negative effects on the body image of individuals who engage in it, as they predominantly portray a lean and toned body figure.…”
Section: Discussionmentioning
confidence: 99%
“…Among the others, the complex relationship between EA, and SMA, perfectionism, body image disorders, and "fitspiration" construct have been studied, since 2015 (46). Interestingly, "fitspiration" diversion into a distortion of body perception could emerge (20,47,48). Although "fitspiration" generally conveys positive messages, the images associated with that may have negative effects on the body image of individuals who engage in it, as they predominantly portray a lean and toned body figure.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the media, advertising, and technology have become powerful influencers in shaping body image ideals among athletes (Holland & Tiggemann, 2016) Social media has emerged as a dominant platform that significantly influences body image perception in athletes. Studies such as the work by Klier et al (2022) and Vandenbosch et al (2022) have explored the concept of "#fitspiration" on social media platforms. These studies found that fitness-focused content, which often idealizes lean and muscular body types, can lead to body dissatisfaction and negative body image among young athletes.…”
Section: Influence Of Media Advertising and Technology On Shaping Bod...mentioning
confidence: 99%
“…The bene ts of resistance training in enhancing muscular functionality and shaping ideal body [101] are likely to gain public recognition through the promotion on SNS, thereby increased participation in resistance training [102]. When comparing the in uence of information in SNS related to sports participation, Klier et al (2022) discovered that, in contrast to endurance sports, team sports, and other exercise, the utilization of SNS for comprehending sport-related information emerged as one of the most powerful predictors for participating in resistance training and as the sole predictive factor for pursuing ideal body [19]. (2005) demonstrates that the strength of individual intention plays a crucial role in mediating the relationship between intention and behaviour.…”
Section: Social Media Has Positive Impact On College Students' Partic...mentioning
confidence: 99%
“…Given the widespread usage of mobile phones and smart wearable devices among college students [105,115], coupled with the increasing dissemination of tness-related content by ' tness Internet celebrities' and sports and tness brands through SNS [116], it is imperative to establish a closer relationship with college students. To achieve this, targeted delivery of timely and effective information based on users' habits in using SNS becomes crucial, ultimately developing positive emotions and promoting willingness to participating in physical activities [19,117]. The present study extends the ndings of previous research, highlighting not only the signi cant in uence of positive emotions has signi cant effect on intention of resistance training and subsequent behaviour maintenance but also emphasizing the potential positive impact of positive emotions induced by SNS on resistance training intention and behaviour.…”
Section: Social Media Has Positive Impact On College Students' Partic...mentioning
confidence: 99%
See 1 more Smart Citation